The Nigerian stock exchange factbook - Nigerian Stock Exchange (Lagos : Nigerian Stock Exchange, 1991)
A factbook about the activities of the Nigerian Stock Exchange.
Vols. for <2002>- accompanied by CD-ROM version.
Description based on: 2012/2013; title from cover.
oif 18/09/14
Ref.
Keywords: Corporations -- Nigeria -- Finance -- Directories; Financial institutions -- Nigeria -- Directories; Stockbrokers -- Nigeria -- Directories; Nigerian Stock Exchange -- Directories